Transport decarbonization in big cities: An integrated environmental co-benefit analysis of vehicles purchases quota-limit and new energy vehicles promotion policy in Beijing. (August 2021) - Yang, Xi; Lin, Wanqi; Gong, Ruixin; Zhu, Mingzhe; Springer, Cecilia
Highlights: The nonnegligible environmental health co-benefit is considered in Beijing road transport sector. Beijing's electric vehicles policy are studied under different level of EV market penetration. The strict electric vehicles policy in Beijing will help the city to fulfil its low carbon city target. The quota-limit policy and EV promotion in Beijing has substantial positive health co-benefit. It provides a reference for effectiveness analysis of administrative decree policy in big cities. Abstract: In the deep decarbonization era against climate change, big cities set ambitious targets for road transport. As China's capital, Beijing has very strict vehicles quota-limit policies. This study contributes to the literature for its innovations on the evaluation of quota-limit executive policy for big cities which few studies have studied, and its improved method with integrated analysis model which distinguish itself for including future co-benefit estimation and enterprise-level data analysis. This study estimates the energy consumption and health environmental co-benefit up to 2030, results show that the ambitious policy will significantly reduce both CO2 and key atmospheric pollutants emissions. Besides, the health economic loss from different illnesses attributed to NOX, CO, PM2.5 and HC will be 65 %, 61 %, 19 % and 57 % lower than reference scenario in 2030. During the energy transition, gasoline will still occupy the biggest proportion of the passenger sector fuel use in Beijing. However, the quota-limit policy will have significant integrated impact on both emission mitigation and avoiding public health damage. This study provides a good reference for big cities in other countries for both its improved method and the effectiveness of administrative decree policy for urban transport planning.